ESCAPE ECHO BIGEMINY SECONDARY TO MILD HYPERKALEMIA - Amran, Iskandar Mirza; Kuppan, Sethujanathran; Chin, Wong Lok (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Escape echo bigeminy is a bigeminal rhythm in which each atrioventricular junctional escape beat is followed by a conducted beat from a sinus P wave. In other words, a normal sinus (anterograde) P wave is sandwiched between 2 QRS complexes, an arrangement causing group beating with recurring couplets. CASE This is the case of a 63-year-old female, with hypertension, Type 2 diabetes mellitus, dyslipidemia, and ischemic heart disease, who consulted with a one-day history of chest discomfort. The chest pain was burning in nature and associated with nausea and vomiting. Upon presentation, the patient was bradycardic with a heart rate of 40 beats per minute and normal blood pressure. An electrocardiogram showed atrioventricular junctional escape beats followed by a conducted beat from a sinus P wave. The chest radiography was normal. She has mild hyperkalemia (5 mmol/L), but other electrolytes were normal. Troponin I was negative. The patient was treated for bradycardia secondary to unstable angina. She was given intravenous atropine for two doses, which did not resolve the bradycardia. The patient was given an insulin chase and serum potassium was reduced to 4 mmol/L. Heart rate normalized to 60 beats per minute and repeated ECG showed resolved escape echo bigeminy. CONCLUSION Escape-capture bigeminy occurs if the effective inter-sinus interval exceeds the sum of the escape interval and the refractory period after the escape beat. This requires an intermittent block of the impulse either at the sinus or AV nodal level. Digitalis, digitalis plus beta-blocker, or calcium blocker may be partially implicated. The patient had mild hyperkalemia and the correction of which led to the resolution of the arrhythmia. As presented by the case, mild hyperkalemia may cause an escape echo bigeminy arrhythmia that can be reversed medically, precluding the need for pacing.